First report of papaya mealybug Paracoccus marginatus (Hemiptera:Pseudococcidae) from Malaysia - Mastoi, Muhammad Ishaque; Adam, Nur Azura; Muhamad Awang, Rita; Abd Ghani, Idris; Ibrahim, Yusof (American-Eurasian Network for Scientific Information, 2011)
Paracoccus marginatus, Williams and Granara de Willink 1992 (Hemiptera: Pseudococcidae) commonly known as papaya mealybug (PMb) is reported for the first time in Malaysia on papaya, cassava, eggplant, Jatropha and hibiscus plants. Four species of chalcidoid parasitoids were observed parasitizing the PMb. Acerophagus papayae was the major parasitoid of PMb. Two common predators namely Apertochrysa sp. and Cryptolaemus montouzieri were also found feeding on PMb.